The Association Between Camellia sinensis Tea Consumption and Reduced Risk of Anxiety Disorder for Covid-19 Survivors: A Cross-Sectional Study among Medical Students - Mohammad Bakhriansyah; Vina Yulia Anhar; Sidnan Naufa Sulaiman; Faishal Muhammad Arrosyad (Fakultas Kedokteran Universitas Lambung Mangkurat, 2023)
Abstract: Negative stigma for Covid-19 survivors might induce anxiety. Camellia sinensis (C. sinensis) tea has been used to treat anxiety but no studies evaluate the tea on risk of anxiety among medical students who were Covid-19 survivors. Hence, we aimed to evaluate the risk of anxiety for C. sinensis tea drinkers among them. A cross-sectional study was conducted at Medical Faculty Universitas Lambung Mangkurat in December 2021. Information about tea consumption was collected from a questionnaire and anxiety disorder was determined by Zung Self-Rating Anxiety Scale. Logistic regression analysis was used to calculate the risk. Of 129 students, 55 students (42.64%) had anxiety. Students who drank tea at least 2 glasses/day had a lower risk of anxiety by 90.4% than non-tea drinkers. Thus, C. sinensis tea was significantly associated with a lower risk of anxiety started from at least 2 glasses/day among medical students who were Covid-19 survivors.